Association Analysis of Neuronal Nitric Oxide Synthase 1 Gene Polymorphism With Psychopathological Symptoms in Chronic Ketamine Users - Chen, Jiansong; Zhang, Minling; Zhou, Chao; Ding, Yi; Fan, Ni; He, Hongbo (Frontiers in Psychiatry, 2020)
Objective: We examined the allelic variants of the gene coding neuronal nitric oxide synthase 1(NOS1)in chronic ketamine users in Chinese population and analyzed the association between NOS1 gene polymorphism and psychopathological symptoms in chronic ketamine users. The association between the NOS1 polymorphism and ketamine use characteristics was also examined. Methods: 197 male chronic ketamine users and 82 controls were recruited. Four common SNPs of NOS1 gene, rs6490121,rs41279104,rs3782206 and rs3782219 were examined by real-time PCR with the TaqMan® assay system. Psychopathological symptoms were assessed using the Positive and Negative Syndrome Scale (PANSS), Beck Depression Inventory (BDI) and the Beck Anxiety Inventory (BAI). Results: The genotype distribution of rs6490121 and rs41279104 in chronic ketamine-users were significantly different from control(p=0.0001 and p=0.002).The G allele frequency of rs6490121 in ketamine users was higher than that in the controls(p=2.23*10-6, OR=3.07, 95%CI=1.93-4.90) . The T allele frequency of rs41279104 in chronic ketamine users was higher than that in the controls (p=0.01, OR=1.76, 95%CI=1.14-2.72). The BAI score was significantly different among the three genotypic groups of rs6490121(F=6.21, p=0.002) in ketamine users, subjects of genotype GG had lower score than subjects of genotype AG.The score of negative symptom subscale of PANSS was significantly different among the three genotypic groups of rs41279104(F=5.39, p=0.005) in ketamine users ,subjects of genotype TT had higher score than subjects of genotype CT. There was no difference in drug use characteristics in different genotype of the four NOS1 gene polymorphisms tested in ketamine users(p>0.05).